Transonic Flow Over an Aerofoil with Spoiler - Kania, W. (Engineering Transactions, 1975)
Experimental tests were made in order to detailed study of two-dimensional flow over an aerofoil with the spoiler. The solid, deflected and slotted spoilers were investigated. The tests were carried out in a transonic wind tunnel at Mach numbers from 0.8 to 1.1 Surface pressure distributions and shadowgraphs were obtained at angles of attack from -4° to 8°. The analysis of the incremental pressure distributions and shadowgraph observations indicated the existence of six regimes of the flow over the aerofoil with spoiler according to the local flow conditions on the aerofoil and to geometric parameters of the spoiler. The lift effectiveness of spoiler defined as the increment of section lift coefficient due to the spoiler is evaluated and its dependence on the test variables is discussed.